Brain-derived Neurotrophic Factor Is Stored in Human Platelets and Released by Agonist Stimulation - Fujimura, Hironobu; Altar, C. Anthony; Chen, Ruoyan; Nakamura, Takashi; Nakahashi, Takeshi; Kambayashi, Jun-ichi; Sun, Bing; Tandon, Narendra N. (Thrombosis and Haemostasis, 2002)
Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, plays critical roles in the survival, growth, and maintenance of brain and peripheral neurons. We report the presence of BDNF protein in human platelets and its release upon agonist stimulation. The BDNF content of washed platelets varied widely, from 3.5 to 67 ng/ 4 X 108 platelets, averaging 25.2 ± 21.2 ng/4 X 108 platelets (mean ± SD). The BDNF concentration in platelet-poor plasma was low (1.7 ± 1.7 ng/ml, n = 11). Thrombin, collagen, the Ca++ ionophore A23187, and shear stress each induced a rapid release of BDNF from platelets. Up to only half of platelet BDNF was secreted upon agonist stimulation, suggesting that platelets may have a non-releasable pool of BDNF, or that the released BDNF binds to a recognition site on the platelet surface and is internalized, as occurs with serotonin. However, the cognate BDNF receptor, TrkB, was not detected in platelets. Nevertheless, the ability of BDNF to bind washed platelets was shown by FACS analysis confocal microscopy and by the binding and apparent internalization of [125I]-BDNF by platelets. A very high affinity site (Kd = 130 X 10−15 M, ∼80 sites/platelet) and a moderately high affinity site (Kd = 20 nM, ∼3750 sites/platelet) were identified. The BDNF content in two mega-karyocytic cell lines, DAMI and Meg-01, was only 0.1% of the content measured in platelets. No BDNF mRNA was detected by Northern blotting in these cell lines or in platelets. The pituitary gland was also ruled out as a source for platelet BDNF, since the BDNF content of rat platelets did not decrease 2 weeks after hypophysectomy. Thus, platelet BDNF is not acquired from the megakaryocyte or pituitary gland, but is probably acquired from other sources via the blood circulation. Platelets appear to bind, store and release BDNF upon activation at the site of traumatic injury to facilitate the repair of peripheral nerves or other tissues that contain TrkB.
Keywords: BDNF; platelets; aggregation; secretion; shear stress